Gullies and Moraines Are Islands of Biodiversity in an Arid, Mountain Landscape, Asgard Range, Antarctica - Solon, Adam J.; Mastrangelo, Claire; Vimercati, Lara; Sommers, Pacifica; Darcy, John L.; Gendron, Eli M. S.; Porazinska, Dorota L.; Schmidt, S. K. (Frontiers in Microbiology, 2021)
Cold, dry, and nutrient-poor, the McMurdo Dry Valleys of Antarctica are among the most extreme terrestrial environments on Earth. Numerous studies have described microbial communities of low elevation soils and streams below glaciers, while less is known about microbial communities in higher elevation soils above glaciers. We characterized microbial life in four landscape features (habitats) of a mountain in Taylor Valley. These habitats varied significantly in soil moisture and include moist soils of a (1) lateral glacial moraine, (2) gully that terminates at the moraine, and very dry soils on (3) a southeastern slope and (4) dry sites near the gully. Using rRNA gene PCR amplicon sequencing of Bacteria and Archaea (16S SSU) and eukaryotes (18S SSU), we found that all habitat types harbored significantly different bacterial and eukaryotic communities and that these differences were most apparent when comparing habitats that had macroscopically visible soil crusts (gully and moraine) to habitats with no visible crusts (near gully and slope). These differences were driven by a relative predominance of Actinobacteria and a Colpodella sp. in non-crust habitats, and by phototrophic bacteria and eukaryotes (e.g. a moss) and predators (e.g. tardigrades) in habitats with biological soil crusts (gully and moraine). The gully and moraine also had significantly higher 16S and 18S ESV richness than the other two habitat types. We further found that many of the phototrophic bacteria and eukaryotes of the gully and moraine share high sequence identity with phototrophs from moist and wet areas elsewhere in the Dry Valleys and other cold desert ecosystems. These include a Moss (Bryum sp.), several algae (e.g. a Chlorococcum sp.) and cyanobacteria (e.g. Nostoc and Phormidium spp.). Overall, the results reported here broaden the diversity of habitat types that have been studied in the Dry Valleys of Antarctica and suggest future avenues of research to more definitively understand the biogeography and factors controlling microbial diversity in this unique ecosystem.